Індивідуалізована протективна вентиляція як фактор зниження ризику розвитку післяопераційних легеневих ускладнень в абдомінальній хірургії - Кузьменко, Тетяна Сергіївна; Воротинцев, Сергій Іванович; Кузьменко, Т. С.; Воротынцев, С. И.; Kuzmenko, T. S.; Vorotyntsev, S. I. (My University, 2017)
В роботі проведена оцінка індивідуалізованої респіраторної підтримки у 50 пацієнтів з помірним або високим за шкалою ARISCAT ризиком розвитку післяопераційних легеневих ускладнень (ПЛУ), що були прооперовані на органах черевної порожнини. Показано, що проведення протективної вентиляції з ДО 7 мл/кг ІдМТ, індивідуалізованим ПТКВ та РМ з досягненням рівня тиску плато (Рplat) 30 см вод. ст. при лапаротомних операціях тривалістю ≥2 годин дозволяє в 3 рази зменшити загальну кількість ПЛУ та достовірно знизити ризик розвитку ателектазів легеневої тканини і пневмоній. В работе проведена оценка индивидуализированной респираторной поддержки у 50 пациентов с умеренным или высоким по шкале ARISCAT риском развития послеоперационных легочных осложнений (ПЛО), которые были прооперированы на органах брюшной полости. Показано, что проведение протективной вентляции с ДО 7 мл/кг ІдМТ, индивидуализированным ПДКВ и РМ с достижением уровня давления плато (Рplat) 30 см вод. ст. при лапаратомных операциях длительностью ≥2 часов, позволяет в 3 раза уменьшить общее количество ПЛО и достоверно снизить риск развития ателектазов легочной ткани и пневмонии. Aim is to evaluate the effectiveness of individualized respiratory support in patients with moderate or high risk of postoperative pulmonary complications (PPCs) in abdominal surgery. Materials and methods. In a prospective randomized study included 50 patients with an estimate on the scale ARISCAT≥26 points, which was conducted by open surgery on the abdominal organs. Patients of group 1 (n=25) during an operation conducted «standard» mechanical ventilation (MV), the patient group 2 (n=25) – protective ventilation of the maneuver recruiting alveoli and use individual values of positive pressure at the end of exhalation (PEEP). In the postoperative period tracked the incidence atelectasis of lung tissue, pneumonia, pneumothorax, pleural effusion and hypoxemia. For the statistical analysis used the program Statistica for Windows 6.0. Results. In group 1 PPCs developed in 9 patients (36%), of which 100% – atelectasis lung tissue in 89% – pneumonia, 44% – pleural effusion and hypoxemia. In group 2 PPCs observed in 3 patients (12%), of which 33% – atelectasis lung tissue, pneumonia and hypoxemia, 100% was available pleural effusion. The relative risk (RR) and odds ratio (OR) of atelectasis in group 2 patients were significantly lower than in group 1 patients (RR=0.11, 95% CI 0.01-0.85 (p<0.05), OR=0.07, 95% CI 0.01-0.67, (p<0.05)). RR and OR development of pneumonia in patients of group 2 were significantly lower than in group 1 patients too (RR=0.13, 95% CI 0.02-0.97, (p<0.05); OR=0.09, 95% CI 0.01-0.81, (p<0.05)). Conclusion. The use of individualized respiratory support significantly reduces the risk of atelectasis lung tissue and postoperative pneumonia in patients with an estimate on the scale ARISCAT≥26 points in abdominal surgery.
Индивидуализированная протективная вентиляция как фактор снижения риска развития послеоперационных легочных осложнений в абдоминальной хирургии
Individualized respiratory support as a factor of reducing the development of post¬operative pulmonary complications in abdominal surgery
Keywords: індивідуалізація респіраторної підтримки; післяопераційні легеневі ускладнення; протективна вентиляція легень; индивидуализация респираторной поддержки; послеоперационные легочные осложнения; протективная вентиляция легких; individualization of respiratory support; postoperative pulmonary complications; protective lung ventilation